Fistula Campaigns-Are They of Any Benefit? - Cetin Cam; Ates Karateke; Arman Ozdemir; Candemir Gunes; Cem Celik; Buhara Guney; Dogan Vatansever (Elsevier, 2010)
Objective: Evaluation of the problems encountered during a voluntarily fistula campaign in a regional hospital of Niger (Africa). Materials and Methods: Women underwent basic gynecological examination, methylene blue testing, and/or direct cystoscopy as necessary. According to their clinical condition, women were informed and surgical options offered as appropriate. Operations were performed under spinal or epidural anesthesia. Immediate postoperative outcomes were followed during the stay of the surgical team in the country. Results: A total of 62 women were examined and 11 had causes of incontinence other than obstetric fistula. In 9.8% of the women, severe local infection precluding any surgical intervention was evident. In 58.8% of patients, the trigonal region and/or urethra were irreversibly damaged. A proportion of patients (9.8%) with large lesions and intact urethra that were offered vaginal layered closure refused the intervention. Of the women that were operated on (21.6%), six underwent vaginal layered closure with Martius fat flap and five women underwent a combined abdomino-vaginal approach. Conclusion: It is extremely difficult to meet the needs of this global problem with short term programs and volunteers. Directing these efforts to specialist fistula centers and creating reliable scientific evidence should be the main goal.